Comparison of somatostatin analog and meta-iodobenzylguanidine radionuclides in the diagnosis and localization of advanced neuroendocrine tumors. - Kaltsas, G; Korbonits, M; Heintz, E; Mukherjee, J; Jenkins, P; Chew, S; Reznek, R; Monson, J; Besser, G; Foley, R; Britton, K; Grossman, AB (2001)
A comparison has been made of [(123)I]meta-iodobenzylguanidine ([(123)I]MIBG) and [(111)In]pentetreotide scintigraphy in 54 patients with a variety of neuroendocrine tumors of whom 46 patients had metastatic disease. [(111)In]Pentetreotide scintigraphy was more sensitive in detecting metastatic lesions, as demonstrated on computed tomography and/or magnetic resonance scanning, than [(123)I]MIBG: 67% vs. 50% for carcinoid tumors (n = 24), 91% vs. 9% for pancreatic islet cell tumors (n = 12), 100% vs. 60% for medullary thyroid carcinomas (n = 5), and 75% vs. 100% for pheochromocytomas/paragangliomas (n = 4). In only 2 patients were lesions seen with [(123)I]MIBG scanning that were not apparent with [(111)In]pentetreotide. With the exception of pancreatic islet cell tumors, both radionuclides exhibited a similar sensitivity in detecting hepatic metastases, whereas in three patients the two radionuclides exerted a complementary role as different deposits exhibited uptake to only 1 or the other radionuclide. Hepatic metastases were the most important clinical predictor of a positive scan for both radionuclides. Neither elevated 5-hydroxyindoleacetic acid levels nor any other hormonal marker was predictive of a positive scan. In 8 patients with clinical and/or hormonal evidence of a neuroendocrine tumor but negative conventional radiology, [(111)In]pentetreotide scintigraphy was more sensitive than [(123)I]MIBG (37.5% vs. 12.5%) in detecting lesions. In conclusion, scintigraphy with [(111)In]pentetreotide detects more metastatic lesions than [(123)I]MIBG in patients with carcinoid and pancreatic islet cell tumors and medullary thyroid carcinomas; [(123)I]MIBG scintigraphy may be more sensitive for sympathoadrenomedullary tumors. The radionuclides may exert a complementary role in the detection and treatment of neuroendocrine tumors in occasional patients, as areas of different pattern of uptake were identified within the same patient. These data have implications not only for staging such tumors, but also for identifying patients who might benefit from treatment using either [(131)I]MIBG or radioactive somatostatin analogs.